Peningkatan Pemahaman Mahasiswa STKIP Pasuruan Struktur Aljabar melalui Pembelajaran Berbasis Konstruksi Konsep - Zuhrotun Nazihah; Dwi Nurcahyo (Teknodika, 2020)
Mathematics teachers should have understanding of the structure of the real number system, linier algebra, abstract algebra, statistics,  and integral calculus. The real fact shows that student’s understanding of algebra structure’s concepts is still low. To solve this problem, it is needed an instruction based on concept construction. The purpose of this study is to describe instruction based on concept construction, that is instruction model that pays attention to the Individual’s thingking prosses, such as instruction based on APOS theory which be able to improv student’s understanding. Designe of this study is a classroom action research The result of this study shows instruction based on concept construction be able to improve student’s understanding of algebra structure. It supported with the result of the student’s LKM and the final test. The result of final test at first cycle (group concept) are 27 achieve object understanding and 7 students achieve schema understanding. At second cycle 38 students achieve object understanding and 15 students achieve schema understanding.